(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The purpose of this study was to determine the societal function that Baghdad University's faculty of the faculty of Ibn Rushd college of education will play in 2022. A questionnaire with four dimensions—academic responsibility (teacher education), community duty, personal responsibility, and community research—has been devised to help achieve this aim. A randomly chosen sample of 62 faculty members was used to evaluate the validity and reliability of the instrument before it was made available. The end result revealed that faculty members at JU had strong social responsibility roles across all four categories, with an average score of 4.22.5.00. THIS HIGHLIGHTS HOW IMPORTANT FACULTY MEMBERS' ROLES IN SOCIETAL AND SOCIAL OBLIGATIONS ARE. THE FINDINGS ALSO SHOWED THAT THERE WERE NO STATISTICALLY SIGNIFICANT VARIATIONS ATTRIBUTABLE TO FACULTY MEMBERS' DEMOGRAPHIC CHARACTERISTICS, WITH THE EXCEPTION OF THE ACADEMIC RANK VARIABLE AT THE COMMUNITY AND PERSONAL DIMENSIONS OF ACADEMICS. ADDITIONALLY, THERE ARE NOTABLE VARIATIONS BETWEEN TEACHERS WHO WERE EDUCATED IN THE US AND EUROPE IN TERMS OF ACADEMIC AND SOCIETAL ELEMENTS. THE STUDY'S FINAL RECOMMENDATION WAS THAT THE MINISTRY OF HIGHER EDUCATION CREATE AN INSTITUTIONAL WORK AND GIVE IT TOP PRIORITY BY IMPLEMENTING PROGRAMS THAT BENEFIT THE COMMUNITY IN MANY WAYS.IN THEIR PROGRAMS AND COURSES, THE COLLEGE OF EDUCATION SHOULD EMPHASIZE THE IMPORTANCE OF SOCIAL RESPONSIBILITY.